Pretreatment of oil palm frond (OPF) by electron beam irradiation and ionic liquid method: article - Nasary, Nurul Faaiqah; Azizan, Amizon (2018)
In this study, the studied lignocellulosic biomass (LCB), oil palm frond (OPF) is pretreated with an ionic liquid (IL), 1-Ethyl-3-methylimidazolium acetate [EMIM]Ac. The pretreatment combines physical and physicochemical pretreatment for dissolving the biomass cellulose. The sample is first pretreated by electron beam irradiation (EBI) at Agensi Nuklear Malaysia which the irradiation dose of 100, 200, 400, 600, 800 and 1000 kGy with 2 MeV of voltage accelerator and 5 mA current flow. Ionic liquid pretreatment is then carried out using Bioshake at temperature 70 - 99°C for 4 hours with the speed of 800 rpm. Until the supernatant is achieved, the sample is being dried in the oven and analyzed by using Fourier Transformation Infrared (FTIR) spectroscopy. FTIR spectroscopy allows the composition of the biomass to be examined, qualitatively and quantitatively based on the absorbance of infrared radiation. TAPPI method is used to determine cellulose, hemicellulose and lignin degradation. The resulting FTIR spectra of the EBI and IL pretreated oil palm frond and cellulose show that the lignocellulosic biomass components degradation increases as the EBI doses increases, yet the spectra reading trend got a fluctuation due to error that possibly caused by contamination and particle size of LCB. The resulting TAPPI method shows that the cellulose composition and lignin degradation increase as the EBI doses increases, nevertheless the reading instability present in the middle of the doses range which probably due to excessive water presence in the ionic liquid and inhibitory factor that prevents the cellulose to be soluble and lignin to be degraded, respectively.